Statistical Evaluation of Pilot’s Behavior Models Parameters Connected to Military Flight Training - Miroslav Jirgl (Energies, 2020)
The paper discusses the possibilities of objective assessment of military flight training quality based on statistical evaluation of pilot’s behavior models parameters. For these purposes, the pilots’ responses to non-standard flight situations were measured by using a fixed-base and a moving-base engineering flight simulator. Tens of military pilots at different training stages were tested. By exploiting real-life tests, we established that the given pilot models provide sufficiently accurate approximation of realistic human responses. Importantly, the models are relatively easy to use, and the individual parameters can be unambiguously interpreted, i.e., the time constants of the pilot behavior model are obtainable, representing the pilot’s current psychological and physiological state of mind. The parameters lay in the defined ranges, and they characterize the ability of the human/pilot to adapt to a controlled dynamic system. Consequently, a fundamental statistical analysis based on pilot’s behavioral model parameters was conducted, using the acquired test data representing the pilot’s behavior during repeated measuring. The initial results indicate the possibility to use the results for objective assessment the military flight training level.